Country-level decision making for control of chronic diseases : workshop summary - Beatty, Alexandra S. (Online access: NCBI NCBI Bookshelf., 2012)
A 2010 IOM report, Promoting Cardiovascular Health in the Developing World, found that not only is it possible to reduce the burden of cardiovascular disease and related chronic diseases in developing countries, but also that such a reduction will be critical to achieving global health and development goals. As part a series of follow-up activities to the 2010 report, the IOM held a workshop that aimed to identify what is needed to create tools for country-led planning of effective, efficient, and equitable provision of chronic disease control programs.